In the first book of ramanujan him find this identity:

Let k , n $\in\mathbb{N}$* and define $A_k=3^k\left(n+\frac{1}{2}\right)-\frac{1}{2}$. the if r is a positive interger

$$\sum_{k=n+1}^{A_r}\frac{1}{k}=r+2\sum_{k=0}^{r-1}\left(r-k\right)\sum_{j=A_{k-1}+1}^{A_k}\frac{1}{\left(3j\right)^3-3j}$$ where $A_{-1}=0$

I want to know a demonstration for that identity, because he uses it to demonstrate his very popular affirmation:

$$\sum_{n=1}^{1000}\frac{1}{n}=7\frac{1}{2} "very\ nearly"$$


First we need the result from entry $2$ of the reference. Lets start with the parial fractions \begin{eqnarray*} \frac{1}{(3j)^3-3j} =\frac{1/2}{3j-1}-\frac{1}{3j}+\frac{1/2}{3j+1}. \end{eqnarray*} So \begin{eqnarray*} 1+2 \sum_{j=1}^{n} \frac{1}{(3j)^3-3j} =1+ \sum_{j=1}^{n} \left( \frac{1}{3j-1}\color{red}{+\frac{1}{3j}}+\frac{1}{3j+1} \color{red}{-\frac{3}{3j}} \right) \\ = \sum_{j=1}^{3n+1} \frac{1}{j} -\sum_{j=1}^{n} \frac{1}{j} = \sum_{j=n+1}^{3n+1} \frac{1}{j} . \end{eqnarray*} Now with $A_k=3^k n + \frac{1}{2} (3^k-1)$ then $A_{k+1}=3A_k+1$, the above result gives \begin{eqnarray*} \sum_{j=A_k +1}^{A_{k+1}=3A_k+1} \frac{1}{j} =1+ 2 \sum_{j=1}^{A_k} \frac{1}{(3j)^3-3j}. \end{eqnarray*} Now sum the above formula from $k=0,1,\cdots, r-1$ and we have \begin{eqnarray*} \sum_{j=n +1}^{A_{r}} \frac{1}{j} =r+ 2 \sum_{k=0}^{r-1} \sum_{j=1}^{A_k} \frac{1}{(3j)^3-3j}. \end{eqnarray*} Note that the inner sums on the RHS are contained within next sum, so this can be rearranged to the result \begin{eqnarray*} \sum_{j=n +1}^{A_{r}} \frac{1}{j} =r+ 2 \sum_{k=0}^{r-1} (r-k) \sum_{j=A_{k-1}+1}^{A_k} \frac{1}{(3j)^3-3j}. \end{eqnarray*}

  • $\begingroup$ what is RHS?... $\endgroup$ – Juan Alfaro Oct 29 '17 at 21:54
  • 1
    $\begingroup$ RHS $=$ right hand side. $\endgroup$ – Donald Splutterwit Oct 29 '17 at 21:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.